(untitled) (Vietnam Journal of Community Medicine, 2025)
association with clinical characteristics, quality of life, and related factors among inpatients receiving traditional medicine treatment. Subject and methods: A cross-sectional study was conducted on 386 inpatients at three hospitals in Ho Chi Minh city from April 2024 to February 2025. Stool types were classified using the Bristol scale. Quality of life was assessed using the EQ-5D-5L instrument. Results: The most common stool type was Bristol type 4 (38.3%), followed by type 3 (21.0%). There were statistically significant associations between stool types and age, gender (p < 0.05). The loose stool group (type 5-7) had significantly higher cholesterol levels than the normal group (p = 0.035). Abnormal stool types tended to have lower EQ-VAS scores, particularly types 1-2 and 6-7. Three quality of life dimensions-mobility, self-care, and usual activities-were significantly associated with stool types (p < 0.05). Conclusion: Stool characteristics are associated with certain clinical indicators and quality of life among inpatients undergoing traditional medicine treatment. Routine assessment of Bristol stool types may enhance comprehensive inpatient care in traditional medicine settings.